2016
DOI: 10.1161/jaha.116.003619
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cardiovascular Health Metrics in Obese Adults: National Health and Nutrition Examination Survey (NHANES), 1988–2014

Abstract: BackgroundNo study has quantified trends in the prevalence of cardiovascular disease risk factors and cardiovascular health metrics among obese people in the United States in recent years.Methods and ResultsWe examined the secular changes in cardiovascular health metrics and key cardiovascular disease risk factors among obese adults (aged ≥20 years) in the United States. We included 18 626 obese adults (body mass index ≥30) from the National Health and Nutrition Examination Survey (NHANES) III and NHANES 1999–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 53 publications
(81 reference statements)
2
34
0
Order By: Relevance
“…Van Minnen et al [19] reported that approximately half (53%) of Results from Bhanji et al [15] are similar to Van Minnen et al [19] with ap-ing weight status respectively. Despite lower agreement among those classified as obese or morbidly obese in the current study, these findings are generally consistent with those from several global settings [13] non, some argue that focus should be placed on physical activity, exercise, and cardiorespiratory fitness, instead of on weight status [47], while others contend the strong association between weight status and health outcomes maintains the value of such measures [49]. Another way fitness level may influence BMI is indirectly through increased muscle mass and decreased fatty tissue.…”
Section: Discussionsupporting
confidence: 84%
“…Van Minnen et al [19] reported that approximately half (53%) of Results from Bhanji et al [15] are similar to Van Minnen et al [19] with ap-ing weight status respectively. Despite lower agreement among those classified as obese or morbidly obese in the current study, these findings are generally consistent with those from several global settings [13] non, some argue that focus should be placed on physical activity, exercise, and cardiorespiratory fitness, instead of on weight status [47], while others contend the strong association between weight status and health outcomes maintains the value of such measures [49]. Another way fitness level may influence BMI is indirectly through increased muscle mass and decreased fatty tissue.…”
Section: Discussionsupporting
confidence: 84%
“…Of the numerous comorbidities linked to obesity, the most common are T2D; a variety of cardiovascular complications such as hypertension, coronary artery disease, and stroke; and certain types of cancer (Guo and Garvey, 2016). Notably, obesity and T2D represent top preventable causes of premature death and disability (Mathers and Loncar, 2006;Bauer et al, 2014), and the World Health Organization estimates that annually approximately 1.5 million deaths are directly attributable to diabetes (WHO, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These four CVD risk factors are the most prevalent in Mexico and have been reported to be even greater than in some of the analyzed countries. In Mexico and India, adults with overweight are respectively 5.25 and 4.15 times more likely to have mixed dyslipidemia and hypertriglyceridemia [37,94], while up to 95.2% of American individuals with obesity have lipid abnormalities [95]. Considering that reductions starting at 1% of the Mexican population's average BMI would save up to $986 million USD in the next years [50], intensive strategies to improve dietary patterns, foster active lifestyles, and increase access to pharmacological treatments that normalize bodyweight and the lipid profile are vital to moderate costs generated by CVD.…”
Section: Cvdmentioning
confidence: 99%